1994
DOI: 10.1172/jci117258
|View full text |Cite
|
Sign up to set email alerts
|

Induction of vascular endothelial growth factor expression by prostaglandin E2 and E1 in osteoblasts.

Abstract: PGE, and PGE2 are potent stimulators of bone formation. Osteogenesis is strongly dependent on angiogenesis. Vascular endothelial growth factor (VEGF), a secreted endothelial cellspecific mitogen, has been implicated in physiological and pathological angiogenesis. The aim of this study was to examine the possible role of VEGF in PG stimulation of bone formation. We found that in rat calvaria-derived osteoblast-enriched cells and in the osteoblastic RCT-3 cell line PGE2 and El increased VEGF mRNA and protein lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
188
2
8

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(212 citation statements)
references
References 49 publications
(33 reference statements)
14
188
2
8
Order By: Relevance
“…Determination of ALP activity was performed as described previously, 12 and the activity was expressed as nanomoles of p-nitrophenol formed per minute per milligram of protein. Hyp contents were evaluated by Woessner's method 13 and were expressed as mg/10 5 cells. von Kossa's staining was processed to monitor the mineralized nodules by using 5% silver nitrate, as described previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of ALP activity was performed as described previously, 12 and the activity was expressed as nanomoles of p-nitrophenol formed per minute per milligram of protein. Hyp contents were evaluated by Woessner's method 13 and were expressed as mg/10 5 cells. von Kossa's staining was processed to monitor the mineralized nodules by using 5% silver nitrate, as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…7 Prostaglandins (PGs) are produced both in skeletal tissue and bone cell culture in response to various stimulus, and are among the most important local factors with autocrine/ paracrine roles in bone. 13 Among the various PGs produced in bone tissue, the most abundant one is prostaglandin E2 (PGE2), and it appears to be of utmost importance in bone physiology. Although PGE2 is initially described as a potent bone-resorbing substance, 14,15 accumulated evidence indicates that PGE2 is a potent stimulator of bone formation in vivo and in vitro.…”
mentioning
confidence: 99%
“…The host microenvironment is thought to influence tumor progression (Fukumura et al, 1997;Gohongi et al, 1999). Immunohistochemical examination of human colorectal cancer tissue has revealed that the marked COX-2 expression was detectable not only in tumor cells but also in inflammatory cells and fibroblasts in the stroma (Harada et al, 1994). It was also reported that COX-2 is abundant in the stromal cells that surround intestinal polyps in mice with a mutated APC gene (Ohshima et al, 1996).…”
Section: Cox-2/vegf and Tumor Angiogenesismentioning
confidence: 99%
“…Previous studies have identified that the growth factors platelet-derived growth factor, transforming growth factor-␤1, and bFGF can each stimulate the production of VEGF (38,39). Cytokines, such as interleukin-1, can induce VEGF transcripts in VSMC (40); nitric oxide can stimulate VEGF mRNA in the lung (41); and E-series prostaglandins can stimulate VEGF production in osteoblasts (42). Hypoxia is one of the best characterized stimuli for the induction of VEGF production by a variety of tumor cells, as well as VSMC, both in vitro and in vivo (12,13,39).…”
Section: Table IImentioning
confidence: 99%